Development of a human antibody fragment cross-neutralizing scorpion toxins. (March 2023) - Romero-Moreno, José Alberto; Serrano-Posada, Hugo; Olamendi-Portugal, Timoteo; Possani, Lourival D.; Becerril, Baltazar; Riaño-Umbarila, Lidia
Abstract: Previously, it was demonstrated that from the single chain fragment variable (scFv) 3F it is possible to generate variants capable of neutralizing the Cn2 and Css2 toxins, as well as their respective venoms ( Centruroides noxius and Centruroides suffusus ). Despite this success, it has not been easy to modify the recognition of this family of scFvs toward other dangerous scorpion toxins. The analysis of toxin-scFv interactions and in vitro maturation strategies allowed us to propose a new maturation pathway for scFv 3F to broaden recognition toward other Mexican scorpion toxins. From maturation processes against toxins CeII9 from C. elegans and Ct1a from C. tecomanus, the scFv RAS27 was developed. This scFv showed an increased affinity and cross-reactivity for at least 9 different toxins while maintaining recognition for its original target, the Cn2 toxin. In addition, it was confirmed that it can neutralize at least three different toxins. These results constitute an important advance since it was possible to improve the cross-reactivity and neutralizing capacity of the scFv 3F family of antibodies. Highlights: Directed evolution improves the affinity of the scFv 3F against scorpion toxins. Novel scFv RAS27 showed cross-neutralization against several scorpion toxins. The combination of scFv RAS27 and 10FG2 complements the neutralizing capacity. scFv RAS27 could give rise to new variants with improved cross-neutralization.